PERENCANAAN DAN PENJADWALAN PRODUKSI DENGAN MENGUNAKAN METODE TRANSPORTASI GUNA MENINGKATIFKAN PROFIT - Ayudina Puji Estrimaz; Junaedi Iskandar (Department Industrial Engineering, University of Muhammadiyah Malang, 2001)
The first step of implementing the planning and schedulling of production usingtransportation method is forecast the demand that oount the number of demand that depend on thetrendo fdata. Recordingto the aralysis,t he fix rnethodw hich appropiatew ith trendo f datai s rnovingaverages, inglee xponenthiaeln dd oublee xponentiaml ethod.T he next stepi s mix datab asedo n theforecastingr esult thet havec onvercedin to hours,a nd changec ost into hours.T he last stepu sing thosedatai nto 85 prcgramt o get a productionp lana ndc osto f planningr esult.F romt he final analysisc anfind decreasincgo sta fteri mplementintgr ansportatiomn ethoda boutR p.-l1.7 65.28Qo,-r 7,27o /oo ff ofthe overall cost.